Environment and Man : Current Studies in Vegetational History at the Geological Survey of Denmark - Th. , Svend; Aaby, Bent; Vad, Bent (Journal of Danish Archaeology, 1983)
Environment and Man - Current Studies in Vegetational History at the Geological Survey of Denmark.